Educação e comunidades quilombolas Laranjituba e África - município de Moju/PA: relação da EJA com costumes e tradições de base africana - Lima, Sandra Helena Ataíde de (2012)
The present study introduces the subject “Education and maroon community: EJA’s relationship with customs and African traditions in the maroon Communities África and Laranjituba in Moju/PA”, conducted in the Caeté’s Maroon Territory. Antonio Olinto’s work, Alma da África trilogy, a literary text that introduces an Africa with its customs and traditions, political, human and cultural issues since the independence of the ancient colonies grounds the customs and African traditions. The main goal is to research if the EJA’s educative process considers the customs and African traditions of Larajituba and África communities. EJA’s study starts during the process of industrialization and concentration at downtown, nearly 30’s, when the Brazilian system of education gets finally consolided. The first stage of the research was realized with a great bibliographical review, by examining written texts about the black people in Pará and EJA searching out about if the educative process really considers those customs and African traditions. The second stage adopted a Collaborative Research, developed in reunions with 28 participants, among teachers, students and parents, who acted in a mutual supportive, with shared goals and agreed by the group involved. The study concluded that in spite of the effort in provide a curricular proposal for EJA, realized by the Moju’s department of education, with a specific methodology for those remaining maroons, there’s still such a lot of efforts so that the educational process in the Laranjituba e África maroon communities practice the specific methodology of the curricular proposal. The research brings a relevant contribution to the EJA’s guidelines of Moju’s county, as well as to the Enhancement and Specialization courses offered by IFPA training that develops in the county of Moju.